Ovarian carcinosarcomas: p53 status defines two distinct patterns of oncogenesis and outcomes - Gurdial Dhillon; Marta Llaurado-Fernandez; Basile Tessier-Cloutier; Keiyan Sy; Dina Bassiouny; Guangming Han; Nelson K. Y. Wong; Kathryn McRae; Mary Kinloch; Jennifer Pors; Laura Hopkins; Allan Covens; et al. (Frontiers in Oncology, 2024)
ObjectivesOvarian carcinosarcoma (OCS) is a rare and lethal type of ovarian cancer. Despite its incredibly poor prognosis, it has received little research attention. In this study, we aim to evaluate the molecular features of OCS and elucidate their clinical significance.Study methodsWe examined 30 OCS by immunohistochemistry (IHC) and targeted panel sequencing collected from a single institution (2003–2013) as the initial molecularly characterized cohort (Cohort A). From November 2016 to April 2023, we collected an additional 67 OCS cases from three institutions across British Columbia and Alberta as the contemporary cohort (Cohort B) for clinical correlation. The Kaplan–Meier method was used to estimate overall and progression-free survival, and differences in survival rates were compared using the log-rank test. All tests were two-sided. A p-value of less than 0.05 was considered statistically significant.ResultsThe majority of OCS (82%) in the initial Cohort A were p53-mutated, and the carcinomatous component displayed the histological and molecular features of a high-grade tubo-ovarian serous carcinoma (HGSC-like). In a minority of OCS, the epithelial components were characteristics of endometrioid or clear cell carcinomas, and IHC staining was wild type for p53. In the contemporary Cohort B, we observed the same histological findings related to the p53 IHC staining pattern. The median overall survival of the p53-mutated HGSC-like OCS (47 patients) was significantly higher (43.5 months) compared with that of the p53 wild-type OCS (10 patients, 8.8 months; P < 0.01). Pathogenic BRCA1/2 germline/somatic mutations were observed in 7 patients (17.5%) of HGSC-like OCS, and all these patients were alive at 3 years from diagnosis compared to a 51% 3-year survival among the patients with BRCA1/2 wild-type HGSC-like OCS (33 patients) (p = 0.022). Majority of patients (6/7) with BRCA1/2-mutated OCS received poly (ADP-ribose) polymerase inhibitor as maintenance therapy in this cohort.ConclusionsMost OCSs have a morphologic and molecular profile resembling HGSC; however, some OCSs display a molecular profile that suggests origin through non-serous oncogenic pathways. This molecular distinction has both prognostic and treatment (predictive) implications. These findings underscore the importance of routine p53 IHC testing on all OCS and BRCA1/2 testing on p53-mutated OCS.